Peran Kelompok Tani Hutan (KTH) Kepuh Dalam Upaya Pelestarian Hutan dan Mata Air Dusun Mendiro - Rehana Mardatila; Annisa Andien Armadhani; Ani Fitri Isnaini; Angelina Rahmawati; Anafi Muhammad; Habib Ahmad; Muhammad Idhom (Lembaga Pengembangan Kinerja Dosen, 2024)
Conservation is about the balance of nature. Panlungan Village, located in Wonosalam Subdistrict, Jombang Regency, has natural potential in the form of abundant forests and springs. However, illegal logging in 1998 damaged Panlungan's forests, reducing the headwaters of the river and increasing the risk of natural disasters such as landslides. Awareness of the importance of forests as a source of oxygen and habitat for various species prompted the local community to form the Kepu Forest Farmer Group (KTH) which focuses on conserving and planting forests with native plants. The Mendiro Settlement spring in Panlungan Village is the main source of livelihood for the local community, but is under serious threat due to man-made environmental degradation. The Kepuh Forest Farmers Group (KTH) has played an active role in the sustainable management of springs since the 1990s, with a focus on protecting the environment and educating the community about the importance of forest ecosystem conservation. This research shows that active community participation in forest and spring conservation is essential to preserve natural resources in Panlungan village. By strengthening supervision of illegal logging activities, strengthening conservation programs, and raising awareness of the importance of maintaining forest ecosystems, we hope to ensure the survival of future generations and the preservation of clean water sources for the people of Panlungan Village.